Assessment of energy efficiency in reheating furnace of a steel plant by using process heating assessment and survey tool (PHAST) - Jha, Manjari; Singh, V K (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Steel is one of the most common materials that we come into contact in our day to day life. The steel industry is the major energy intensive industry among all industries, which emits large amount of greenhouse gases (GHG). These GHG carry energy in the form of heat along with them, have very harmful impact on the environment as well as result in direct economical loss for the industry. The present study assesses energy efficiency in a steel manufacturing company, namely Jayasawal’s NECO Industries Ltd. at Siltara Raipur, with the help of process heating assessment and survey tool (PHAST). Overall efficiency determined in the reheat furnace was 44.66%. Flue gas losses were the biggest energy losses in the reheat furnace, accounting for 40.2% of the total energy losses during full production.